Calendrier, représentations mentales et procédures de calcul chez les Nahuas (Mexique) - Marie-Noëlle Chamoux (Journal de la Société des Américanistes)
Calendar, mental representations and computation procedures among the Nahuas (Mexico). For determining important dates of feasts related to All Saints’ Day or All Souls’ Day, the Nahuas of Huauchinango (Puebla) formerly used a system of timemarks which was in fact very precise, so long as it is not judged according to our habits of sequential numeration. Instead, one must reconstruct the topological representations underlying this system. The « peasants’ time » is not always this « floating time » defined by Lucien Febvre.